Effects of international relations on foreign direct investment:Acase study of Uganda investments Authority (UIA) - Kemigisha Irene (Uganda Christian University, 2024)
The study examined the effects of international relations on foreign direct investment in Uganda: a case of Uganda Investments Authority (UIA). The study was guided by objectives which included; finding out relations between Uganda and investor countries, identifying important treaties to improve the investment climate in Uganda, and finding out the importance of negotiations on foreign direct investments in Uganda. The study was carried out using a case study design with a qualitative research approach. The data were collected using interviews during the data collection, purposive sampling method was used. A group of 18 respondents who are top management and staff of Uganda Investments Authority (UIA) were used as a sample during the study. The study established that the Ugandan investment strategy is highly dependent on the country’s robust diplomacy with these influential partners like China, the United State, and the United Kingdom that seek to foster long-term partnerships for the two parties. These partnerships are very critical in enhancing Uganda’s economic development, technology transfer and foreign investment. Also, some agreements like the Bilateral Investment Treaties, East African Community Common Market Protocol, and the African Continental Free Trade Area have also benefited Uganda in enhancing the legal structure and market access which might take some time to reap results. Nevertheless, some constraints arising in the negotiation process in Uganda Investment Authority are bureaucratic delay, legal formalities, and culture barrier are terms that suggest the need for better communication and clearing of procedures that would make the Ugandan environment more attractive to the foreign investors. Finally, the study suggested that there was a need to enhance and diversify Uganda’s foreign alliances by building up the existing partnerships and seeking new ones outside the existing major associates. They also suggested that there is much more that can be done with international treaties and agreements, coupled with the need to eliminate bottlenecks experienced during negotiation with foreign investors through the usage of more effective and efficient methods.